Development of a Self‐Adhesive Oleogel Formulation Designed for the Slow Release of Semiochemicals. Issue 10 (19th August 2022) - Muskat, Linda C.; Jiang, Lin; Brikmann, Johannes; Rostás, Michael; Patel, Anant V.
Abstract: Oleogels have been widely studied as delivery matrices for lipophilic compounds. Despite their potential, oleogels are underexplored for the formulation and release of semiochemicals for insect behavior manipulation strategies. An ethylcellulose‐candelilla wax‐oleogel as a suitable carrier for the slow release of volatile semiochemicals, employing the sesquiterpene β ‐caryophyllene as a model substance is presented. A current drawback of ethylcellulose oleogels is the high temperature needed during the oleogel preparation procedure, leading to excessive volatilization of the active compounds. Reducing the gelling temperature from 104.8 to 66.9 °C and, thus, the volatile addition temperature by addition of the softener octyldodecanol results in 95.28% entrapment efficiency. Experimental results demonstrate release modifiability by tailoring the matrix crystalline state due to candelilla wax addition. Furthermore, a method is established for analyzing the self‐adhesive properties of the gel on plant leaves. In addition, the gel's self‐adhesive properties employed on apple leaves are synergistically affected by oil leakage and gel stiffness. Olfactometer experiments showed that the formulation is able to enhance the attractiveness of aphid‐infested plants for parasitic wasps. The present study provides a novel matrix‐type semiochemical formulation based on non‐toxic, biobased and biodegradable materials and will contribute to the establishment of oleogels as delivery systems for semiochemicals. Abstract : An ethylcellulose‐candelilla wax‐oleogel is designed combining unique properties such as a reduced processing temperature, high entrapment efficiency, improved oil binding capacity, mechanical and shape stability, self‐adhesive properties on leaves, and release modifiability, making it highly suitable for semiochemical formulation and release. This study contributes to the establishment of oleogels as delivery matrices for various semiochemicals.